Rapid-onset obesity with hypothalamic dysfunction, hypoventilation and autonomic dysregulation (ROHHAD): a case with additional features and review of the literature - Chew, H B (BMJ Publishing Group, 2011)
A rare syndrome of rapid-onset obesity with hypothalamic dysfunction, hypoventilation and autonomic dysregulation (ROHHAD) has been recently described. We report the first patient with this syndrome in Southeast Asia and review reported cases to date. Our patient was good health with normal development until the age of 2. He then developed hyperphagic obesity, hypersomnolence, seizures, alveolar hypoventilation, central hypothyroidism, sodium and water dysregulation, gastrointestinal dysmotility, strabismus, disordered temperature and irregular heart rate, altered sweating, delayed puberty, mental retardation and recurrent respiratory tract infections. The cardiomyopathy with heart failure and abnormal cerebral spinal fluid (CSF) neurotransmitter analysis present in our patient have not been reported previously. Tumours of the sympathetic nervous system are known to be associated with this syndrome but had not been found in our patient at the time of reporting. We highlight the difficulty of achieving the diagnosis of ROHHAD syndrome and its overlap with other well-established disease entities. The mortality and morbidity resulting from the high incidence of cardiorespiratory arrest may be prevented by early ventilatory support.